2011
DOI: 10.1258/om.2011.100080
|View full text |Cite
|
Sign up to set email alerts
|

Operative delivery rates following induction of labour for obstetric cholestasis

Abstract: Summary: The aim of this study was to determine whether women induced for obstetric cholestasis (OC) have increased rates of operative delivery compared with women without OC who are induced. This retrospective case-control study included 64 women with OC (singleton pregnancies), who had labour induced compared with two control groups (matched for parity and gestational week at delivery). The majority of women were induced at 37 weeks. We found no significant increase in the rate of operative or assisted deliv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 4 publications
0
3
0
Order By: Relevance
“…A case–control study (64 cases) 50 and case‐cohort study (348 cases) 51 both showed no increased risk of postpartum haemorrhage in women with ICP. Standard care using national guidance for the third stage of birth should be followed 33 .…”
Section: How Should Women Be Advised On Timing and Mode Of Birth?mentioning
confidence: 93%
See 1 more Smart Citation
“…A case–control study (64 cases) 50 and case‐cohort study (348 cases) 51 both showed no increased risk of postpartum haemorrhage in women with ICP. Standard care using national guidance for the third stage of birth should be followed 33 .…”
Section: How Should Women Be Advised On Timing and Mode Of Birth?mentioning
confidence: 93%
“…Women and pregnant people with ICP do not have increased rates of assisted or operative birth compared with women without ICP 50 . Mode of birth should therefore be based on usual obstetric or medical indications.…”
Section: How Should Women Be Advised On Timing and Mode Of Birth?mentioning
confidence: 99%
“…Moreover, the majority of early deliveries are induced and there is no evidence that this results in higher rates of emergency cesarean delivery. Indeed, it has been shown in two retrospective cohorts and one prospective study that rates of operative and instrumental delivery are not increased in women with ICP after labor induction (78)(79)(80).…”
Section: Management: Treatmentmentioning
confidence: 99%